Enhancement of sawing strategy of multiple surface quality characteristics in low power fiber laser micro cutting process on titanium alloy sheet. (February 2020) - Pramanik, D.; Kuar, A.S.; Sarkar, S.; Mitra, S.
Highlights: Laser micro cutting of Ti alloy which is based on a new laser sawing strategy. To reduce kerf taper and surface roughness in low power laser beam through cutting. Response surface methodology (RSM) is used in this experiment. This research has a great impact to modify/ enhancement of new laser sawing machine. Abstract: Being a promising non-traditional micro machining process laser micromachining may efficiently and fruitfully be used for hard machining materials without the hindrances of their hardness, toughness and brittleness. Superior specific strength, corrosion resistance and creep properties have made titanium alloy fit for many engineering applications as well as in medical purposes. High quality of cutting metal sheets to achieve intricate shapes and geometries etc has made laser to be an attractive tool and a popular mode. High cutting speed, high accuracy, narrow kerf and least material waste are the reasons for its high quality. Study and experimental analysis of the effect of sawing angle and constant Z height movement with other process parameters like power setting, duty cycle, scanning speed and pulse frequency related to the kerf taper and surface roughness of the 1 mm titanium alloy sheet (Ti-6Al-4V) have been done. Investigations on laser cutting for the attainment of optimization have found out better process control and better quality of final product.